Perkembangan Bahasa pada Anak Usia Dini 4-5 Tahun Ditinjau dari Aspek Sintaksis dan Pragmatik di TK Anggrek Kencana Batang - Wiratnaningsih Wiratnaningsih (Jurnal Kualita Pendidikan, 2021)
This study was conducted to describe the development of language in children aged 4-5 years at TK Anggrek Kencana Batang, especially in the fields of syntax and pragmatics. This research uses descriptive qualitative research method. Examples of this research are two children in class A Tk Anggrek Kencana Batang. From the example of the two children, it is known that the syntactic and pragmatic aspects of children experience different developments. The author concludes that early childhood 4-5 years experience differences in the development of syntactic and pragmatic language. So, the researcher recommends that teachers understand the differences in these developments and stimulate students according to their development so that they continue to improve. Data was collected through interviews, observation, and documentation. The results of this study indicate that aspects of language are very important to be developed in every child who is still in the developmental stage. Because children's language skills are very influential on other aspects of child development. Early education has an important role in developing children's potential. The teacher must use a method that is in accordance with the child's learning pattern. Every child has their own needs and effective learning patterns.